Variation in caesarean section rates in Cyprus, Italy and Iceland: an analysis of the role of the media - Hadjigeorgiou, Eleni; Spyridou, Andria; Christoforou, Andri; Iannuzzi, Laura; Giovinale, Silvia; Canepa, Matilde M.; Morano, Sandra; Jonsdottir, Sigridur Sia; Karlsdóttir, Sigfrídur Inga (My University, 2018)
INTRODUCTION: Cyprus has Europe's highest rate of births by caesarean section (cS). In 2015 56% of all babies were born by cS. This compares with 36% in italy, and 16% in Iceland, which is among the lowest rates in Europe. There is some evidence that cS rates are partly driven by maternal request and media representation. The aim of this review is to explore the depiction of childbirth by CS in the media, and more specifically in newspapers, television, web and informational leaflets in Cyprus, Italy and Iceland. Evidence ACQUISITION: a thematic review of the depiction of cS in the media of Cyprus, italy and Iceland was carried out through an examination of newspapers, television, web, and informational material published or presented in the included countries in 2017. Materials were identified by searches in PubMed and Google Scholar, using pre-determined key words, inclusion and exclusion criteria, and inclusion was agreed by at least two of the authors. Key themes in each data source were triangulated with each other and between the three countries. EVIDENCE SYNTHESIS: The review comprised 81 articles, 10 videos, six birth shows, two informational leaflets and one scientific paper. The central themes WERE: 1) CS as risky and unnecessary intervention, failure of maternity system; 2) cS as a necessary, life-saving intervention; 3) the ethical dimensions of cS; 4) the changing landscape of childbirth and medicalization; and 5) informed choices. In both Cyprus and italy, the media focus was on a need to reduce high levels of cS. The focus in Iceland was on normal birth and midwife led care. The differing media messages in the three countries could partly explain the differing cS rates, suggesting that high cS rates are a social phenomenon, rather than a result of clinical need. The media may have a significant influence on the beliefs and choices of maternity service users, their families, and society in general, as well as health professionals and policy makers. CONCLUSIONS: Those working in the media have an ethical responsibility to critically examine the impact of high national cS rates, and to report on solutions that could optimize both the safety and the wellbeing of mothers and babies.
Keywords: Caesarean section; Communications media; Hospital education department; Prenatal education; Social perception